Efficient overcoming strategies for the challenges faced in sidestream deammonification: Large-stage field experience - Choi, Dae hee; Cho, Kyung jin; Jung, Jin young (Elsevier BV, 2022)
This study aimed to investigate the challenges based on field experience and their corresponded overcoming strategies in a single-stage sequencing batch reactor for deammonification process. During operating the pilot deammonification for 580 days, several challenges were faced that seriously deteriorated nitrogen removal performance. First, chemical-based dewatering system increased heavy metal concentrations in influent wastewater, which inhibited the microbial activity. Second, selective retention of anaerobic ammonium oxidation (ANAMMOX) biomass was required. Third, an unforeseen inflow of anaerobic digestion sludge caused various mechanical problems, which resulted in process failure. Fourth, the lack of experiences in the construction of large-scale reactors resulted in low energy efficiency. To overcome these challenges, we applied various operational strategies (i.e., changing dewatering system, use of newly developed physical microorganism separator (PMS) device, bio-augmentation, residual nitrite control, energy optimization, etc.). As a result, the single-stage deammonification was successfully operated with a high nitrogen removal rate (0.7 kg/m3/d) and low energy consumption (1.2 ± 0.1 kW h/kg N).